CRIMINOLOGICAL ANALYSIS OF WOMEN'S INVOLVEMENT IN ILLEGAL CIRCULATION OF NARCOTICS - Ahmad, Akhiruddin (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
Research Objectives 1). To know and understand the background back women are involved in the illicit trafficking of narcotics. 2). To know and understand the forms of women's involvement in illicit drug trafficking. 3). To find out the efforts made by the Women's Correctional Institution involved in the illicit trafficking of Narcotics (Drugs). The results of the research are the Correctional Institution in providing guidance to Narcotics Prisoners in Correctional Institutions, namely by carrying out many development program activities, namely independence programs, personality programs, national and state awareness programs, programs to reunite society so that inmates can return to being good human beings. useful for themselves family and religion and when they return to society, they can be accepted again. The programs are: First, there is an independence development program, where this program is carried out so that inmates can work and have their own skills for their provision. For example, opening a bicycle repair shop, carp cultivation, catfish farming, cricket cultivation, bird farming, tilapia cultivation, ginger cultivation, multicultural cultivation, cattle farming, goat farming, and for female prisoners there is also knitting and making handicrafts. Second, there is a personality development program, where this program is carried out so that the inmates can get closer to God, so that the inmates can restore good mentality so that when they leave they can be accepted back into society. Examples include mutual cooperation, helping each other, reminding each other about prayer and eating schedules. The three programs are awareness of the nation and state, where this program is carried out so that prisoners can love their homeland Indonesia again and can regenerate a sense of nationalism in them, for example, such as flag ceremonies, direction of relevant agencies on the 1945 constitution. Fourth, the program reunites the community, where this program is carried out so that the inmates when they leave the Penitentiary can be accepted back into the community, with all the knowledge that has been given in the Correctional Institution.